(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Image vision has been studied by many perspectives. It not only important study of graphics but use in multidisciplinary fields. it provide reliability and less chance of hacking or theft while transferring or transporting the data and moreover if we decrypt it and then zip it or break and fuse the original image into various pixel then it will maintain the data transfer speed and avoid the traffic jam situation and fusion of data provide the reliability and safety of the data. it expands from raw data recording into techniques and ideas combining digital image processing, pattern recognition, machine learning and computer graphics and mobile computing especially it is useful for the data safety while transferring the data in traffic jam it minimize the chances of image and data lost during the congestion and articulation point in traffic jam.